2001
DOI: 10.1542/peds.107.4.706
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inhaled Antiinflammatory Therapy on Hospitalization and Emergency Department Visits for Children With Asthma

Abstract: Inhaled antiinflammatory therapy is associated with a significant protective effect on the risk for hospitalization and ED visits in children with asthma. Cromolyn and ICSs were associated with similar effects on risks.asthma drug therapy, inhaled antiinflammatory agents, health maintenance organizations, hospitalization, emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(121 citation statements)
references
References 25 publications
7
112
1
1
Order By: Relevance
“…Earlier work has shown that hospital admissions and emergency department visits account for a substantial proportion of healthcare costs [33]. In the present study there were no hospitalisations or visits to the emergency department room for acute severe asthma, confirming that with the appropriate control of asthma, morbidity, hospitalisation and emergency department visits can be reduced [17,18]. For other populations with less optimal control the cost analysis may be less favourable.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Earlier work has shown that hospital admissions and emergency department visits account for a substantial proportion of healthcare costs [33]. In the present study there were no hospitalisations or visits to the emergency department room for acute severe asthma, confirming that with the appropriate control of asthma, morbidity, hospitalisation and emergency department visits can be reduced [17,18]. For other populations with less optimal control the cost analysis may be less favourable.…”
Section: Discussionsupporting
confidence: 73%
“…In previous studies, it was shown that a reduction in healthcare utilisation, such as emergency department visits and hospitalisations, can be achieved with adequate asthma control [17,18]. Furthermore, maintenance treatment with inhaled corticosteroids has been shown to be cost effective [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, a baixa adesão ao tratamento com esses medicamentos tem sido associada à elevada freqüência de hospitalizações e atendimentos em serviços de pronto-socorro 3 .…”
Section: Introductionunclassified
“…5,7 Acknowledging the high rates of acute care visits for asthma, the Institute of Medicine has identifi ed asthma as an ambulatory care-sensitive condition. …”
Section: Introductionmentioning
confidence: 99%
“…1,4 Asthma is one of the most common reasons for hospital admission among children. 1,5 Appropriate use of controller medications can reduce asthma exacerbations, acute care visits for asthma, and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%